Lyman continuum escape fraction in Ly α emitters at z ≃ 3.1. (11th January 2020) - Bian, Fuyan; Fan, Xiaohui
ABSTRACT: We measure the Lyman continuum (LyC) escape fraction in 54 faint Lyman-alpha emitters (LAEs) at $z$ ≃ 3.1 in the GOODS-South field. With the average magnitude of R = 26.7 AB ( M UV = −18.8 and L ≃ 0.1 L *), these galaxies represent a population of compact young dwarf galaxies. Their properties are likely to resemble those in the galaxies responsible for reionizing the Universe at $z$ > 6. We do not detect LyC emission in any individual LAEs in the deep HST F336W images, which covers the rest-frame 820 Å. We do not detect the LyC emission of these LAEs in the stacked F336W images either. The 3σ upper limit of LyC escape fractions is $f_{\rm esc}\lt 14\!-\!32{{\ \rm per\ cent}}$ . However, the high Ly α rest-frame equivalent width (EW), low stellar mass, and UV luminosity of these LAEs suggest that they should have $f_{\rm esc}\gt 50{{\ \rm per\ cent}}$ . The low LyC escape fraction from this work and other stacking analyses suggests that the LyC-leaking galaxies with $f_{\rm esc}\gt 50{{\ \rm per\ cent}}$ at $z$ = 2–3 do not follow the relation between f esc and UV luminosity and Ly α EW derived from typical galaxies at similar redshifts. Therefore, the UV luminosity and Ly α EW are not the best indicators for the LyC escape fraction.